Integrating geographic information systems into library services a guide for academic libraries - Abresch, John.; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
This book integrates traditional map librarianship and contemporary issues in digital librarianship within a framework of a global embedded information infrastructure, addressing technical, legal, and institutional factors such as collection development, reference and research services, and cataloging/metadata, as well as issues in accessibility and standards.
I. Geography and librarianship / John Abresch, Ardis Hanson, Susan Heron, Peter Reehling -- II. Information economy and geospatial information / John Abresch, Peter Reehling, Ardis Hanson -- III. Spatial databases and data infrastructure / John Abresch, Peter Reehling, Ardis Hanson -- IV. Describing geospatial information / Ardis Hanson, Susan Heron -- V. From print formats to digital / Ardis Hanson, Susan Heron -- VI. Accessibility / Ardis Hanson -- VII. Reference services / Ardis Hanson -- VIII. Collection management issues with geospatial information / John Abresch, Ardis Hanson, Peter Rheeling -- IX. Geographic information and library education / John Abresch, Ardis Hanson, Peter Rheeling -- X. What the future holds / John Abresch, Ardis Hanson, Susan Heron, Peter Rheeling.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on Jun 24, 2010).
Keywords: Libraries -- Special collections -- Geographic information systems; Geographic information systems; Electronic books